Earthquake Rupture Arrest from Depth-Dependent Frictional Stability on the Pütürge Segment of the East Anatolian Fault Zone, Turkiye (Turkey) - Nevitt, Johanna M.; Jeppson, Tamara N.; Bilham, Roger; Moore, Diane E.; Lockner, David A.; Barnhart, William D.; Cakir, Ziyadin; Ayruk, Efe Turan; Brooks, Benjamin A.; Ruth, Dawn; Ekhtari, Nima; Gomez, Francisco G.; et al. (SEISMOLOGICAL SOC AMER, 2026)
Determining why earthquake ruptures stop is a central challenge in earthquake science and seismic hazard assessment. The P & uuml;t & uuml;rge segment of the East Anatolian Fault Zone, T & uuml;rkiye, exhibits shallow creep ( 6.5 earthquake ruptures at greater depth. Here, we evaluate whether variations in frictional stability along this segment aided arrest of the 2020 M 6.7 Elazi & gbreve; and 2023 M 7.8 Pazarc & imath;k earthquake ruptures. Analysis of Sentinel-1 Synthetic Aperture Radar imagery indicates the 2023 M 7.8 rupture propagated laterally into a metamorphic massif within the P & uuml;t & uuml;rge segment, where slip rapidly decayed below detection limits. Creepmeters along this segment recorded no significant surface afterslip (<3 mm) in the following year. To investigate this fault-slip behavior, we conducted triaxial friction experiments on P & uuml;t & uuml;rge fault gouge sampled from an outcrop exposure. The gouge, composed primarily of muscovite, quartz, and calcite, is velocity strengthening at conditions approximating 0-2.5 km depth and velocity weakening at 4-5 km depth. This transition to velocity-weakening friction is associated with enhanced comminution and shear localization observed microstructurally. Our results suggest that depth-dependent frictional stability of the P & uuml;t & uuml;rge fault segment facilitates rupture nucleation and propagation at depth while maintaining rupture-arresting behavior near Earth's surface.
Keywords: GOUGE; Geochemistry & Geophysics